ДОСЛІДЖЕННЯ ДИНАМІЧНИХ ЯКОСТЕЙ ВАНТАЖНИХ ПОЇЗДІВ, ОБЛАДНАНИХ КОЛЕСАМИ З РІЗНИМИ ПРОФІЛЯМИ ПОВЕРХОНЬ КОЧЕННЯ - KOVTUN, O. M.; MALIY, V. V. (текст 3, 2025)
DOI: https://doi.org/10.15407/itm2025.02.105 The importance of this work stems from the necessity to renew the Ukrainian freight rolling stock with the aim to increase train operation safety and improve the dynamic performance and the wheel-rail interaction of trains moving at increased speeds on tracks with different parameters. The renewal will contribute to the solution of the important problem facing the Ukrainian railway transport: speeding up the integration of Ukraine into the European railway service. Because of this, increased attention should be paid to theoretical studies aimed to dynamic performance improvement. Such studies should consider train motion on tracks with different parameters and estimate dynamic performance on tangents and in curves. This paper presents theoretical estimates of the dynamic performance of a freight train on Kryukovsky Railway Car Building Works’ 18-7020 trucks of axle load 230 kN. The estimates were obtained for an elastoplastic inertial tangent and curved track with account for external disturbances caused by rail geometry imperfection (R65 rails of cant 1/20 on the Ukrainian railways and UIC60 rails of cant 1/40 on the European railways). The trucks were considered to be equipped with wheels of different profiles: the home standard one, the European one, and a new one developed at the Institute of Technical Mechanics of the National Academy of Sciences of Ukraine and the State Space Agency of Ukraine. It was shown that the use of the new wheel profile does not result in exceeding the admissible values of the dynamic indices when moving at service speeds on tangents and in curves both on the Ukrainian and on the European railways. At the same time, the new wheel profile offers a far longer wheel life due to wear reduction. REFERENCES 1. Lazaryan V. A. Dynamics of Transport Vehicles. Kiev: Naukova Dumka. 1985. 528 pp. (In Russian). 2. Ukrainian State Standard 7598:2014. Feight wagons. General requirements to calculation and designing of the new and modernized 1520 mm gauge wagons (non-self-propelled). Introduced on July 1, 2015. Kyiv: UkrNDNTs, 2014. 162 pp. (In Ukrainian). 3. Ukrainian State Standard EN 13848-5:2018 (EN 13848-5:2017, IDT). Railway applications. Track. Track geometry qualities. Part 5. Geometric quality levels. Plain line. 2018. (In Ukrainian). 4. Ushkalov V. F., Malysheva I. Yu., Mashchenko I. A., Pasichnik S. S. Comprehensive retrofit of freight car running gears. Vagonnyi Park. 2007. No. 2. Pp. 18-22. (In Russian). 5. Mokrii T. F., Malysheva I. Yu., Pasichyk S. S. Wheel profile of a freight car with prospective trucks for the combined operation on the Ukrainian and European railways. Teh. Meh. 2023. No. 4. Pp. 90-103.https://doi.org/10.15407/itm2023.04.090